Effectiveness of State Hospitals Forensic Medicine Units in Forensic Medicine Services the Experience of Kocaeli - Çolak, Başar; Yalçın, İlkgül Demirbaş and İğci, Gülfem (The Bulletin of Legal Medicine, 2009)
Forensic medicine services are a part of healt service serving the judicial system. Majority of the forensic medicine services conducted by forensic medicine specialists are served through Forensic Medicine Units within the Ministry of Justice Council of Forensic Medicine. In this study, we aimed to determine the effectiveness of services of forensic medicine at the Forensic Medicine Unit of Kocaeli State Hospital. Reports (n= 1406) prepared in Forensic Medicine Unit of the Kocaeli State Hospital between 01 July 2005 and 31 December 2007, were retrospectively evaluated. Of cases 41.1% were women and %58.9 were men. Mean age was 36.1 + 23.6. While the cases of crimes toward violation of untouchable body were most frequent (43.4%) within the evaluated reports, determinations of age were 22.8%, and forensic psychiatric reports were 19.9%. Of cases, 336 (23.9%) were noted to have been treated in one of the clinics of Kocaeli State Hospital before the preparation of their forensic reports. It was noted that in 44.7% (n = 629) of the cases other specialists were consulted or further diagnostic tests were ordered during the preparation of the reports. In 195 cases, previous reports regarding life threatening events could be obtained for comparison with the final reports. When the findings were compared with the previous reports, 34 (17.4%) cases had wrong findings in their reports in terms any life threatening condition. We found that the demands of reports were from units other than forensic authorities or police station in 349 (24.8%) cases. Among all forensic cases, only 6.2% cases were evaluated at Kocaeli State Hospital Forensic Medicine Unit; we concluded that this unit has not been effectively utilized by forensic authoritites. Key word: Forensic medicine unit of state hospital, forensic medicine specialist, forensic report, organization of forensic medicine service, Kocaeli